Avaliação das ações extensionistas na percepção dos beneficiários: proposição e desenvolvimento de um instrumento de mensuração em instituições de ensino superior - Gibicoski, Silviana Delavechia (2025)
Extension activities represent the connection between educational institutions and society, promoting the transfer and exchange of knowledge with the community (LISBÔA FILHO, 2022). Aiming to assess this relationship from the community’s perspective, the study investigated in the literature the theme of evaluating extension activities, seeking to measure this interaction. The research problem identified was: How can extension activities be evaluated from the perspective of beneficiaries in a Higher Education Institution? The general objective was defined as proposing an evaluative instrument capable of measuring the perception of beneficiaries at a Higher Education Institution. The study adopted a mixed-methods approach, both qualitative and quantitative, with a descriptive character. In the qualitative stage, semistructured interviews were conducted with the proponents of extension activities, aiming to understand their perceptions and contributions regarding the questionnaire applied to beneficiaries. In the quantitative stage, an instrument composed of 21 questions was applied to assess the beneficiaries’ perception of the extension actions developed by the Federal Institute Farroupilha. Data collection took place between May and June 2025, resulting in 198 respondents. The analysis included a description of the participants’ profiles and variables, followed by exploratory factor analysis, which identified three constructs: “Beneficiary Expectations,” “Community Impact,” and “Value Added by the Activity,” all presenting reliability indexes (Cronbach’s Alpha) above 0.848. Subsequently, confirmatory and discriminant factor analyses were conducted, confirming the adequacy of the model and the validity of the data. The results showed that the evaluative instrument, named the Extension Activities Perceived Value Instrument, demonstrated validity in measuring the value attributed by beneficiaries to extension activities. For the analysis, a classification table was developed with five levels of interpretation of perceived value, ranging from very low to very high, using a five-point Likert scale, complemented by a circular graphic representation with a progressive scale and an indicative thermometer. The instrument developed represents an innovation by enabling the measurement of beneficiaries’ perceptions regarding the impacts of extension activities on their personal, professional, and community lives. In this context, understanding the community’s expectations and needs is essential for extension initiatives to be effective and generate positive social impact. The study sought to contribute to the improvement of extension practices, offering Higher Education Institutions support for more assertive planning and strengthening their institutional commitment to social transformation.